2020
DOI: 10.22146/ijbiotech.54092
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced astaxanthin production by oxidative stress using methyl viologen as a reactive oxygen species (ROS) reagent in green microalgae Coelastrum sp.

Abstract: Microalgae are known to be a potential resource of high-value metabolites that can be used in the growing field of biotechnology. These metabolites constitute valuable compounds with a wide range of applications that strongly enhance a bio-based economy. Among these metabolites, astaxanthin is considered the most important secondary metabolite, having superior antioxidant properties. For commercial feasibility, microalgae with enhanced astaxanthin production need to be developed. In this study, the tropical gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…3 , Fig. S2 ) with the absorbance maxima at 480 nm (personal communication from Dr. Tharek, A 18 , Fig. S3 ) and 474 nm 19 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 , Fig. S2 ) with the absorbance maxima at 480 nm (personal communication from Dr. Tharek, A 18 , Fig. S3 ) and 474 nm 19 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, astaxanthin production by Coelastrum sp. was shown to be enhanced by methyl viologen as the reactive oxygen species enhancer 18 . In case of Monoraphidium strain, previous study improved the photoautotrophic culture condition and outdoor cultivation method for increasing the astaxanthin content in Monoraphidium GK12 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that astaxanthin production in Coleastrum sp. was enhanced through the introduction of ROS as a stress inductor into the cultivation medium, which increased production by 1.3-fold (Tharek et al 2020). Nitrogen (N) and phosphorous (P) are both essential for algal growth and therefore play an important role in astaxanthin productivity (Fan et al 2021; Li et al 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several strategies have been employed for a more economical algae culture in increasing the levels of astaxanthin production in green microalgae. Significant efforts have been undertaken to improve astaxanthin production by selecting high yield strains, optimize cultivation and uses of chemicals as metabolic enhancers of astaxanthin [ 16 , [ 50 ] 17 ] . Nevertheless, the progress of this improvement method has yet to be fully satisfied.…”
Section: Introductionmentioning
confidence: 99%